Indirect Flow Diversion for Off-Centered Bifurcation Aneurysms and Distant Small-Vessel Aneurysms, a Retrospective Proof of Concept Study From Five Neurovascular Centers - Schob, Stefan; Brill, Richard; Siebert, Eberhard; Sponza, Massimo; Schüngel, Marie-Sophie; Wohlgemuth, Walter Alexander; Götz, Nico; Mucha, Dirk; Gopinathan, Anil; Scheer, Maximilian; Prell, Julian; Bohner, Georg; et al. (Frontiers in Neurology, 2022)
Background Treatment of cerebral aneurysms using hemodynamic implants such as endosaccular flow disruptors and endoluminal flow diverters has gained significant momentum during recent years. The intended target zone of those devices is the immediate interface between aneurysm and parent vessel. The therapeutic success is based on the reduction of aneurysmal perfusion and the subsequent formation of a neointima along the surface of the implant. However, a subset of aneurysms - off-centered bifurcation aneurysms involving the origin of efferent branches and aneurysms arising from peripheral segments of small cerebral vessels - oftentimes cannot be treated via coiling or implanting a hemodynamic implant at the neck level for technical reasons. In those cases indirect flow diversion - a flow diverter deployed in the main artery proximal to the parent vessel of the aneurysm - can be a viable treatment strategy, but clinical evidence is lacking in this regard. Materials and methods Five neurovascular centers contributed to this retrospective analysis of patients who were treated with indirect flow diversion. Clinical data, aneurysm characteristics, anti-platelet medication and follow-up results, including procedural and post-procedural complications, were recorded. Results 17 patients (mean age: 60.5 years, range: 35-77 years) with 17 target aneurysms (vertebrobasilar: n=9 ) were treated with indirect flow diversion. The average distance between the flow diverting stent and the aneurysm was 1.65mm (range: 0.4-2.4mm). In 15/17 patients (88.2%), perfusion of the aneurysm was reduced immediately after implantation. Follow ups were available for 12 cases. Delayed opacification (OKM A3: 11.8%), reduction in size (OKM B1-3: 29.4%) and occlusion (D1: 47.1%) were observable at the latest investigation. Clinically relevant procedural complications, adverse events in the early phase and in the late subacute phase were not observed in any case. Conclusion Our preliminary data suggest that indirect flow diversion is a safe, feasible and effective approach for off-centered bifurcation aneurysms and distant small-vessel aneurysms. However, validation with larger studies including long term outcomes and optimized imaging is warranted.